A therapist-guided smartphone app for major depression in young adults: A randomized clinical trial - Anu Raevuori; Tero Vahlberg; Tellervo Korhonen; Outi Hilgert; Raija Aittakumpu-Hyden; Valerie L. Forman‐Hoffman (2021)
Meru Health Program (MHP) is a therapist-guided, 8-week intervention for depression delivered via smartphone. The aim was to test its efficacy in patients with clinical depression in a Finnish university student health service.Patients (n=124, women 72.6%, mean age 25y) were stratified based on antidepressant status, and randomized into intervention group receiving MHP plus treatment as usual (TAU), and control group receiving TAU only. Depression, measured by the Patient Health Questionnaire-9 (PHQ-9) scale, was the primary outcome. After baseline (T0), follow-ups were at mid-intervention (T4), immediately post-intervention (T8); 3 months (T20), and 6 months (T32) post-intervention.The intervention group and control group did not have significant differences in depression outcomes throughout end of treatment and follow-up. Among secondary outcomes, increase in resilience (d=0.32, p=0.03) and mindfulness (d=0.57, p=0.002), and reduction in perceived stress (d=-0.52, p=0.008) were greater in MHP+TAU versus TAU at T32; no differences were found in anxiety, sleep disturbances, and quality of life between groups. Post-hoc comparisons of patients on antidepressants showed significantly greater reduction in depression at T32 for MHP+TAU versus TAU (d=-0.73, p=0.01); patients not on antidepressants showed no between-group differences.Limitations include unknown characteristics of TAU, potential bias from patients and providers not being blinded to treatment group, and failure to specify examination of differences by antidepressant status in the protocol.Most outcomes, including depression, did not significantly differ between MHP+TAU and TAU. Exploratory analysis revealed intervention effect at the end of the 6-month follow-up among patients on antidepressant medication.